Analisis Pesan Dakwah Dalam Film Tuhan Izinkan Aku Berdosa - Natasya Natasya; AbdurRazaq AbdurRazaq; Muslimin Muslimin (Jurnal Kajian Islam dan Sosial Keagamaan, 2024)
Today, the world has entered the digital age and the publishing industry has changed. Education is more than moving learning from the bench to the table. However, you can also make calls using voice and video calls. One of them is movies. Film is a form of communication that entertains and inspires people. Movies can change. This means that it can be viewed by all social classes. Film is a combination of images, sound, and images to convey action. It is also included in the film that this method uses the invention of Roland Barthes. Qualitative research is a form of research that uses a descriptive method to seek to understand a phenomenon or phenomenon. Based on the analysis mentioned in the previous section. The artwork by diva Esegun Ako Bardos shows that the artwork doesn’t just convey a sweet message. But it also means something different. Through the many symbols in the film, the film attempts to portray a wide range of religious themes. Instead, it combines social and political issues and ideologies into a single lesson. The film attempts to present a more nuanced view of religion from the perspective of aesthetics.